Intelligent Transport Systems, From Research and Development to the Market Uptake 4th EAI International Conference, INTSYS 2020, Virtual Event, December 3, 2020, Proceedings - Martins, A.; Ferreira, J. (2021)
This book constitutes the proceedings of the 4th International Conference on Intelligent Transport Systems, INTSYS 2020, which was held in December 2020. Due to COVID-19 pandemic the conference was held virtually. With the globalization of trade and transportation and the consequent multi-modal solutions used, additional challenges are faced by organizations and countries. Intelligent Transport Systems make transport safer, more efficient, and more sustainable by applying information and communication technologies to all transportation modes. The 16 revised full papers in this book were selected from 38 submissions and are organized in three thematic sessions on mobility; applications; simulation and prediction.